Development of 3D Microvascular Networks Within Gelatin Hydrogels Using Thermoresponsive Sacrificial Microfibers. Issue 7 (4th February 2016) - Lee, Jung Bok; Wang, Xintong; Faley, Shannon; Baer, Bradly; Balikov, Daniel A.; Sung, Hak‐Joon; Bellan, Leon M.
Abstract : A 3D microvascularized gelatin hydrogel is produced using thermoresponsive sacrificial poly( N ‐isopropylacrylamide) microfibers. The capillary‐like microvascular network allows constant perfusion of media throughout the thick hydrogel, and significantly improves the viability of human neonatal dermal fibroblasts encapsulated within the gel at a high density.